2022
DOI: 10.3390/v14051082
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Immune Responses in SARS-CoV-2-Infected Patients: A Comprehensive Overview

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first detected in humans more than two years ago and caused an unprecedented socio-economic burden on all countries around the world. Since then, numerous studies have attempted to identify various mechanisms involved in the alterations of innate and adaptive immunity in COVID-19 patients, with the ultimate goal of finding ways to correct pathological changes and improve disease outcomes. State-of-the-art research methods made it possible to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 167 publications
(283 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, it was noted that key alterations in peripheral blood circulating B cell populations during the acute phase of SARS-CoV-2 infection were linked to the decreased levels of the relative and absolute number of B cells, increased frequencies of plasma cell precursors, atypical CD21-negative and activated B cells etc. [49,51,52]. Currently, we have shown that vitamin D supplementation could effectively decrease the relative numbers of activated CD38++CD27 transitional B cells and 'naïve' B cells in patients with acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was noted that key alterations in peripheral blood circulating B cell populations during the acute phase of SARS-CoV-2 infection were linked to the decreased levels of the relative and absolute number of B cells, increased frequencies of plasma cell precursors, atypical CD21-negative and activated B cells etc. [49,51,52]. Currently, we have shown that vitamin D supplementation could effectively decrease the relative numbers of activated CD38++CD27 transitional B cells and 'naïve' B cells in patients with acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been carried out recently to study the level of monocyte subsets in response to COVID-19 infection. A higher percentage of CD14+CD16+ inflammatory monocytes was demonstrated in patients with mild to severe COVID-19 ( 20 , 31 ). They also showed that there is a significant expansion of CD14+CD16+monocytes producing IL-6 in the peripheral blood of ICU COVID-19 patients than those who did not require ICU hospitalization.…”
Section: Discussionmentioning
confidence: 96%
“…The detection of immune cells in the peripheral blood at low counts in response to viral infections is attributed to the migration of immune cells to the site of infection or due to the virus-mediated destruction of T cells ( 2 ). In addition, few studies of SARS-CoV-2 infection found that T cells specifically correlate with protection and decreased total lymphocytes, T lymphocyte, and B lymphocyte were associated with severe illness ( 7 , 18 , 19 ) and this decrease is probably caused by a defect in the induction of acquired immunity ( 20 ). In a recent study, the frequency of SARS-CoV-2 specific T cells was equal in vaccinated subjects and patients recovered from COVID-19 ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations